Endothelial dysfunction in heart failure with normal systolic function, and its correction with a metabolic agent, mildronate - V. P. Geychenko; A. V. Kuryata; O. V. Muzhchil (Российский кардиологический журнал)
To assess the influence of a metabolic agent, mildronate, on endothelial function in chronic heart failure (CHF) with normal systolic function, 105 patients with I-IIA Stage, II-III Functional Class (FC) CHF, and normal left ventricular systolic function, were examined. CHF developed as a result of II-III Stage essential arterial hypertension, combined with coronary heart disease (CHD): I-III FC stable angina, and post-infarction cardiosclerosis in 13% of participants, aged 45-86 years. Group I included 50 patients receiving basic therapy: ACE inhibitors, beta-blockers, diuretics, vasodilatators; group II - 55 patients who additionally received a metabolic medication, mildronate. Follow-up period lasted up to 30 days. Endothelial function was assessed by brachial artery Doppler sonography (reactive hyperemia test; "Sonos-100" device), and by measuring blood stable pool of NO metabolite - NO2 (biochemical method by Green L.C. et al). CHF patients demonstrated the signs of endothelial dysfunction: decreased plasma concentration of NO; increased N02 level in red blood cells; reduced endothelium-dependent vasodilatation; vasospastic reactions; in 25% of participants, vasoconstrictory reactions in reactive hyperemia test. Basic CHF therapy resulted in disbalanced NO system activation, endothelial hyperstimulation and dysfunction. Adding mildronate to basic therapy resulted in NO system normalization, and endothelial vasoregulatingfunction improvement, that increased treatment effectiveness